EFEKTIVITAS EMBARGO DALAM MENDORONG DEMOKRATISASI DI MYANMAR (Faculty of Social Science, Universitas Negeri Semarang, 2013)
International pressure on the junta in Myanmar (in particular the American, UN and Europe embargo) becomes positive signal to the democracy movement in the country, although effective or not is still questionable. Notto mention the matter is completed, the pessimism of development of democracy in Myanmar is reinforced by the approach of two new giant in the world economy (India and China); and